A Novel Intraoperative Ultrasound Probe for Transsphenoidal Surgery: First-in-human study. (April 2022) - Cabrilo, Ivan; Delaunay, Rémi; Heaysman, Clare L.; Ourselin, Sebastien; Vitiello, Valentina; Vercauteren, Tom; Marcus, Hani J.; Dorward, Neil L.
Background . Ultrasound has been explored as an alternative, less bulky, less time-consuming and less expensive means of intraoperative imaging in pituitary surgery. However, its use has been limited by the size of its probes relative to the transsphenoidal corridor. We developed a novel prototype that is more slender than previously reported forward-viewing probes and, in this report, we assess its feasibility and safety in an initial patient cohort. Method . The probe was integrated into the transsphenoidal approach in patients with pituitary adenoma, following a single-centre prospective proof of concept study design, as defined by the Innovation, Development, Exploration, Assessment and Long-Term Study (IDEAL) guidelines for assessing innovation in surgery (IDEAL stage 1 – Idea phase). Results . The probe was employed in 5 cases, and its ability to be used alongside the standard surgical equipment was demonstrated in each case. No adverse events were encountered. The average surgical time was 20 minutes longer than that of 30 contemporaneous cases operated without intraoperative ultrasound. Conclusion . We demonstrate the safety and feasibility of our novel ultrasound probe during transsphenoidal procedures to the pituitary fossa, and, as a next step, plan to integrate the device into a surgical navigation system (IDEAL Stage 2a – Development phase).